Follicular Dendritic Cell Sarcoma of the Tonsil - Eun, Young Gyu; Kim, Sung Wan; Kwon, Kee Hwan (Yonsei medical journal, 2010)
Follicular dendritic cell sarcoma (FDCS) is unusual, and those with an extranodal origin in the head and neck region are extremely rare. To date, no cases of tumors featuring the characteristics of follicular dendritic cells were reported in Korea. We report a new case of FDCS of the tonsils in a 65-year-old man. A diagnostic tonsillectomy was performed. Based on histopathologic and immunohistochemical findings, the patient was diagnosed with FDCS. Adjuvant radiotherapy was performed due to a high mitotic count. The patient survived with a 2-year disease free period. The differential diagnosis of a tonsillar mass must include FDCS. In cases in which FDCS is suspected on histopathologic examination, an immunohistochemical study is essential for the diagnosis.